Wolf's isotopic response: A case of dermatomal granuloma annulare after COVID‐19 vaccination - Negar Esfandiari; Patrick Benson; Keith Morley (Wiley, 2023)
Abstract The SARS‐CoV‐2 pandemic was announced in March 2020, with the first vaccines becoming available later that year. Although generally well tolerated, there have been reports of skin reactions occurring after receiving COVID‐19 vaccines, with a rare occurrence of granuloma annulare. Granuloma annulare can occur secondarily to herpes zoster infection in a phenomenon known as Wolf's isotopic response (WIR). WIR has been described to often occur after herpes zoster virus infection, at the location of the healed shingles rash, termed 'post‐herpetic isotopic response' (PHIR). We present the first reported case of PHIR with granuloma annulare after the Moderna COVID‐19 vaccination series. This reported reaction should not limit receipt of the COVID‐19 vaccine, but awareness of this association can minimise additional work‐up and treatment.